2018
DOI: 10.1044/2018_jslhr-l-17-0447
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Lexical Decisions in Developmental Language Disorder: A Meta-Analysis of Behavioral Studies

Abstract: Results broadly support the hypothesis that children with DLD have difficulty in forming detailed lexical representations relative to age- though not language-matched peers. However, further work is required to determine the performance profiles of potential subgroups and the impact of manipulating different lexical characteristics, such as the position and degree of nonword error, phonotactic probability, and semantic network size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…For the SLI group, there does not appear to be a speed-accuracy trade-off in the articulatory suppression condition as faster planning was not coupled with poorer accuracy. Similarly, research has indicated that SLI group deficits in lexical decision tasks are not attributable to a speed-accuracy trade-off (Jones & Brandt, 2018). On the other hand, we found relatively better language ability was associated with slower planning time and greater accuracy for the TD group in the articulatory suppression condition.…”
Section: Study Limitationssupporting
confidence: 76%
“…For the SLI group, there does not appear to be a speed-accuracy trade-off in the articulatory suppression condition as faster planning was not coupled with poorer accuracy. Similarly, research has indicated that SLI group deficits in lexical decision tasks are not attributable to a speed-accuracy trade-off (Jones & Brandt, 2018). On the other hand, we found relatively better language ability was associated with slower planning time and greater accuracy for the TD group in the articulatory suppression condition.…”
Section: Study Limitationssupporting
confidence: 76%
“…Although our data for the subgroup of younger children point into a similar direction, the group comparisons including all children did not show differences between monolingual and bilingual children. As described above (Jones & Brandt, 2018), the difficulty to classify pseudowords correctly depends on the way of pseudoword manipulation. The more difficult a task becomes, the more likely slight uncertaintiesfor example, due to the acquisition of two or more languages, might become visible.…”
Section: Discussionmentioning
confidence: 99%
“…Abilities in word form processing can be investigated through word form-related tasks such as auditory lexical decision (LDT; Claessen & Leitão, 2012; Hein & Kauschke, 2020; Jones & Brandt, 2018; Ripamonti, Lucchelli, Lazzati, Martini & Luzzatti, 2017), rapid naming (RNT; Dixon et al, 2020; Hein & Kauschke, 2020; Messer & Dockrell, 2006), and rhyming (Spencer, Doyle, McNeil, Wambaugh, Park & Carroll, 2000; van Goch, McQueen & Verhoeven, 2014). The LDT enables the assessment of the quality of stored word form representations (Claessen & Leitão, 2012) in the phonological input lexicon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may appear reasonable to assume a causal association between low-level frequency discrimination deficits and the deficits in higher-order speech representation and retrieval that characterise DLD. Children affected by DLD commonly require more exposures to a spoken word than control children in order to encode similar levels of phonological detail (Gray, 2003), for instance, and are often slower and less accurate than age-matched peers when retrieving words and naming known objects (Kambanaros et al, 2015;Messer & Dockrell, 2006), when determining whether an auditory stimulus is a known word or non-word (Jones & Brandt, 2018), when fixing their gaze to a named visual stimulus (McMurray, Klein-Packard, & Tomblin., 2019), when identifying words from clipped auditory segments (Montgomery, 1999), when identifying mispronunciations (Alt & Suddarth, 2012), and, as previously discussed, when repeating non-words (Bishop et al, 1996). These performance deficits between children with and without DLD may be explained in terms of lower familiarity with the target stimuli among children with DLD, which is itself a function of the quality of the speech representations that these children have formed.…”
Section: Rethinking Working Memory Capacity Deficits In Dldmentioning
confidence: 99%